Analysis of the effects of alloying with Si and Cr on the properties of manganese austenite based on AB INITIO modelling - Prysyazhnyuk, Pavlo; Shlapak, Liubomyr; Semyanyk, Iryna; Kotsyubynsky, Volodymyr; Troshchuk, Liubomyr; Korniy, Sergiy; Artym, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2020)
This paper reports a study into estimating the impact of dissolved Si and Cr on the crystalline structure, certain mechanical characteristics, and stability of manganese austenite. The theoretical study was based on the first-principle calculations within a density functional theory (DFT) for austenite structures, which were modeled in the form of 2×2×2 superlattices based on a face-centered cubic lattice. Atoms in the model superlattices were arranged considering the experimental results from analyzing the Mossbauer spectrum and the X-ray phase analysis of experimental alloys corresponding to high manganese steels. The superlattices that represented the structure of the alloyed austenite contained the C atom in the central octahedral pore, which, relative to the Si(Cr) and Mn atoms, was located in the first and second coordinating spheres, respectively. The analysis of calculation results reveals that the dissolution of Si and Cr in manganese austenite leads to an increase in the stability of the austenite phase, both according to the results from modeling within the DFT and based on the findings from the thermodynamic analysis. At the same time, the austenite phase is transferred to the region of plastic materials according to the ratio of the volumetric elasticity to shear modules of ≥1.75 (a B/G criterion). Determining the density of electronic states shows that among the structures studied, the lowest number of electrons at the Fermi level, which indicates the highest electrochemical stability, is characterized by manganese austenite alloyed by Cr. The results of this study provide grounds for expanding the systems of alloying high manganese steels by introducing a significant amount (up to 10 at. %) of Si and Cr, in particular for the application of wear, shock, and corrosion-resistant coatings by the method of electric arc surfacing